Development of learning media for volleyball passing techniques using the articulate storyline application - Hendro Saputro; Guntum Budi Prasetyo; Risfandi Setyawan (Sriwijaya Journal of Sport, 2023)
Based on the results of the needs analysis conducted at Tamansiswa High School, Mojokerto City, articulate storyline-based learning media is needed in learning volleyball basic movement skills to improve learning outcomes and student interest in learning. So, this study aims to develop learning media in the form of learning applications using articulate storylines. The research method used is research. The population of this study was 89 students. The research instrument used a questionnaire for three validators, and a student questionnaire. The data analysis technique used quantitative descriptive with percentage score results. The average value of the evaluation results from learning experts is 87.5% (very valid), volleyball experts are 80.7% (very valid), and multimedia experts 80.4% (very valid). The results of the test to students increased in value from 50% to 71.46%. From these data, it can be concluded that the development of volleyball bottom passing learning devices using the articulate storyline application can be used as a learning medium for tenth grade students.